Pengaruh Pengoperasian Reaktor Kartini terhadapKadar DO, BOD, dan COD Air Pendingin primer - Agus Budhie Wijatna (Faculty of Engineering, Universitas Gadjah Mada, 2004)
Affiliation—Country—Bio Statement Principal contact for editorial correspondence. NameTri Wulan Tjiptono Affiliation—Country—Bio StatementPusat Penelitian dan Pengembangan Teknologi Maju - BATAN, Yogyakarta NameTony Dwi Susanto Affiliation—Country—Bio StatementFakultas Teknik Industri, UPN Veteran, YogyakartaTitle and AbstractTitle AbstractIn light water reaclor (LWR) systems, water coolant passes through reactor core to remove heat generated by fission processes. Therefore, the temperature of water coolant raise and thewater coolant is irradialed by neutrons from reactor core.The research was directed to explorethe influences of both of them to the contents of Dissolved Oxygen (DO), Biological OrygenDentand (BOD) and Chemical Oxygen Demand (COD).The research wss done by chemical titration method to measure the content of DO, BOD5,and COD in the water coolant in which the reactor was operated at critical condition andconstant power. water samplingwere done after 45',90', l3s', IB0',225', and 270', reactoroperation.The results of this research are: (1) the temperature of the coolant is increasing asoperating time function, (2) the content of DO is also increasing, while BOD5 and COD tends tobe constant, and (3)in general the reactor water coolant is safe to be released to the environment.Keywords: water coolant, heat, irradiation, chemical titration, DO